Host and pathogen genetic diversity shape vaccine-mediated protection to Mycobacterium tuberculosis - Cohen, Sara B.; Plumlee, Courtney R.; Engels, Lindsay; Mai, Dat; Murray, Tara A.; Jahn, Ana N.; Alexander, Bridget; Delahaye, Jared L.; Cross, Lauren M.; Maciag, Karolina; Schrader, Sam; Durga, Kaitlin; et al. (Frontiers in Immunology, 2024)
To investigate how host and pathogen diversity govern immunity against Mycobacterium tuberculosis (Mtb), we performed a large-scale screen of vaccine-mediated protection against aerosol Mtb infection using three inbred mouse strains [C57BL/6 (B6), C3HeB/FeJ (C3H), Balb/cx 129/SvJ (C129F1)] and three Mtb strains (H37Rv, CDC1551, SA161) representing two lineages and distinct virulence properties. We compared three protective modalities, all of which involve inoculation with live mycobacteria: Bacillus Calmette-Guérin (BCG), the only approved TB vaccine, delivered either subcutaneously or intravenously, and concomitant Mtb infection (CoMtb), a model of pre-existing immunity in which a low-level Mtb infection is established in the cervical lymph node following intradermal inoculation. We examined lung bacterial burdens at early (Day 28) and late (Day 98) time points after aerosol Mtb challenge and histopathology at Day 98. We observed substantial heterogeneity in the reduction of bacterial load afforded by these modalities at Day 28 across the combinations and noted a strong positive correlation between bacterial burden in unvaccinated mice and the degree of protection afforded by vaccination.Although we observed variation in the degree of reduction in bacterial burdens across the nine mouse/bacterium strain combinations, virtually all protective modalities performed similarly for a given strain-strain combination. We also noted dramatic variation in histopathology changes driven by both host and bacterial genetic backgrounds. Vaccination improved pathology scores for all infections except CDC1551. However, the most dramatic impact of vaccination on lesion development occurred for the C3H-SA161 combination, where vaccination entirely abrogated the development of the large necrotic lesions that arise in unvaccinated mice. In conclusion, we find 2 that substantial TB heterogeneity can be recapitulated by introducing variability in both host and bacterial genetics, resulting in changes in vaccine-mediated protection as measured both by bacterial burden as well as histopathology. These differences can be harnessed in future studies to identify immune correlates of vaccine efficacy.